The Impact of Social Anxiety on University Students in Pakistan: An Islamic Perspective on Student Learning and Well-Being in Higher Education - Wajid, Hassan; Kainaat, Farah; Ullah, Dr. Hafiz Ahmed (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
This study investigates the consequences of social anxiety on the learning experiences and general well-being of university students across 20 different universities in Pakistan, from an Islamic viewpoint, with a focus on trends and prospects beyond 2020. The study investigates how social anxiety affects students' mental health and social interactions in the classroom, which runs counter to the Islamic principle of fostering a supportive and inclusive community (Ummah). Data from online questionnaires completed by 787 students are used in the study. Known as a "hidden struggle," social anxiety still affects a large percentage of students worldwide, including those in Pakistan. These students could find it difficult to ask for assistance from the faculty, engage in class discussions, or connect with their peers—difficulties that go counter to Islam's teachings on acquiring knowledge (Ilm) and forming close social relationships. The study's conclusions, which demonstrate that comparable social anxiety patterns are common in Pakistani academic institutions, address these worldwide issues. This highlights the critical need for more focused treatments that are in line with Islamic ideas of mutual assistance and ease of getting help, such as peer support groups and mental health counseling. It also emphasizes how critical it is to increase awareness of mental health issues in higher education and provide more comprehensive support systems so that students may succeed in their academic and personal lives while adhering to Islamic principles of mental health and community service.